Quality and Equitable Access: Insights from Indonesia - Brewis, Elisa (International Higher Education, 2019)
Sustainable Development Goal 4 calls for equal access to quality higher education. How this can be achieved in practice remains a major policy question. This article presents the case of accountability reform in Indonesia, offering insights as to how the twin policy objectives of teaching quality and equitable access can be addressed. Evidently, accountability mechanisms have empowered the state to regulate both teaching quality and equitable access. The key is holding both state and private institutions to account to maximize system-wide impact.